Persepsi Pemustaka terhadap Brand Positioning dalam Meningkatkan Citra Perpustakaan Proklamator Bung Hatta Bukittinggi - Syah, Rizky Erman; Marlini, Marlini (Lembaga Yasin AlSys, 2024)
The purpose of this study is to describe how the perception of users of brand positioning in improving the image of the library Proklamator Bung Hatta Bukittinggi. The type of research used is quantitative research with descriptive methods. The population in this study is a member of the library that has been registered in the library of the Proklamator Bung Hatta Bukittinggi amounting to 16,673 people. The sampling technique used is simple random sampling. The number of samples in this study as many as 80 samples using the slovin formula with a precision of 10%. In this study, researchers used questionnaires as an instrument. Data collection technique is done by distributing questionnaires to all research samples with data analysis techniques include normality test, linearity test, correlation test, and T test. The results showed that brand positioning has a significant relationship to the image of the library. Brand positioning variable (X) has a relationship to the image library (Y) with the t test shows the sig. of 0.000 < 0.005 and the value of t count of 40.976 > t table 1.987.